THE INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) ON EMPLOYEE PERFORMANCE MEDIATED BY EMPLOYEE ENGAGEMENT IN NURSES AT DIAN HUSADA HOSPITAL, MOJOKERTO - Dian Lestari Putri (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
This research aims to analyze the Organizational Citizenship Behavior (OCB) possessed by nurses at Dian Husada Hospital Mojokerto, whether it is able to influence Employee Engagement and Employee Performance so that it improves the performance of Dian Husada Hospital Mojokerto. The sample used in this research was 80 nurses taken using the convenience sampling technique. Meanwhile, the data analysis technique used is Structural Equation Modeling (SEM) which is adapted to the research conceptual framework. The results of this research are that OCB has a positive and significant effect on Employee Engagement, OCB has a positive and significant effect on Employee Performance, Employee Engagement has no effect on Employee Performance, and OCB has no significant effect on Employee Performance mediated by Employee Engagement.Keywords: Organizational Citizenship Behavior, Employee Engagement, Employee Performance